Analysis of the fibroblast growth factor receptor (FGFR) signalling network with heparin as coreceptor: evidence for the expansion of the core FGFR signalling network. (13th March 2013) - Xu, Ruoyan; Rudd, Timothy R.; Hughes, Ashley J; Siligardi, Giuliano; Fernig, David G.; Yates, Edwin A.
<x xml:space="preserve">Abstract</x> The evolution of the fibroblast growth factor (FGF)–FGF receptor (FGFR) signalling system has closely followed that of multicellular organisms. The abilities of nine FGFs (FGF‐1 to FGF‐9; examples of FGF subfamilies 1, 4, 7, 8, and 9) and seven FGFRs or isoforms (FGFR1b, FGFR1c, FGFR2b, FGFR2c, FGFR3b, FGFR3c, and FGFR4) to support signalling in the presence of heparin, a proxy for the cellular heparan sulfate coreceptor, were assembled into a network. A connection between two FGFRs was defined as their mutual ability to signal with a particular FGF. The network contained a core of four receptors (FGFR1c, FGFR2c, FGFR3c, and FGFR4) with complete connectivity and high redundancy. Analysis of the wider network indicated that neither FGF‐3 nor FGF‐7 was well connected to this core of four receptors, and that divergence of a precursor of FGF subgroups 1, 4 and 9 from FGF subgroup 8 may have allowed expansion from a three‐member FGFR core signalling system to the four‐member core network. This increases by four‐fold the number of possible signalling combinations. Synchrotron radiation CD spectra of the FGFs with heparin revealed no overall common structural change, suggesting the existence of distinct heparin‐binding sites throughout the FGFs. The approach provides a potential method of identifying agents capable of influencing particular FGF–FGFR combinations, or areas of the signalling network, for experimental or therapeutic purposes.